2020
DOI: 10.1186/s12974-020-01744-1
|View full text |Cite
|
Sign up to set email alerts
|

Zerumbone ameliorates behavioral impairments and neuropathology in transgenic APP/PS1 mice by suppressing MAPK signaling

Abstract: Background: Alzheimer's disease (AD) is a major clinical problem, but there is a distinct lack of effective therapeutic drugs for this disease. We investigated the potential therapeutic effects of zerumbone, a subtropical ginger sesquiterpene, in transgenic APP/PS1 mice, rodent models of AD which exhibit cerebral amyloidosis and neuroinflammation. Methods: The N9 microglial cell line and primary microglial cells were cultured to investigate the effects of zerumbone on microglia. APP/PS1 mice were treated with … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 96 publications
(113 reference statements)
3
18
0
Order By: Relevance
“…Taken together, these results indicate that zerumbone can inhibit microglial activation. In a recent study by Li et al, zerumbone inhibited the production of NO and pro-inflammatory cytokines as well as amyloid β-induced activation in a LPS-treated murine microglia cell line (N9) and primary microglia [31]. Li et al reported zerumbone to be effective in an APP-PS1 transgenic mouse model of Alzheimer's disease [31].…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results indicate that zerumbone can inhibit microglial activation. In a recent study by Li et al, zerumbone inhibited the production of NO and pro-inflammatory cytokines as well as amyloid β-induced activation in a LPS-treated murine microglia cell line (N9) and primary microglia [31]. Li et al reported zerumbone to be effective in an APP-PS1 transgenic mouse model of Alzheimer's disease [31].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the effects of zerumbone were studied by Li et al [ 57 ] both in vivo and in vitro. In the in vivo experiment, transgenic APP/PSEN1 mice received daily gavage of zerumbone for 20 days.…”
Section: Effects Of Ginger In Ad Studiesmentioning
confidence: 99%
“…As in previous studies, western blot analysis was carried out [9,24]. One part of the hippocampal tissue obtained from the experimental mice was lysed and homogenized using RIPA buffer containing 1% protease inhibitor cocktail and 2% PMSF.…”
Section: Western Blotmentioning
confidence: 99%
“…The activation of chronic glial and the production of pro-inflammatory cytokine stimulate neurodegenerative, which are observed in AD patients and animal models [ 7 ]. Inflammation activated microglia and astrocytes produce tumor necrosis factor-alpha (TNF-α) and nitric oxide (NO) to exacerbate neuronal damage in several neurodegenerative diseases [ 8 , 9 ]. Activated microglia and astrocytes produce interleukin (IL)-6 and IL-1β to increase the level of amyloid-beta precursor protein (APP) and promote Aβ deposition in AD mice models [ 10 ].…”
Section: Introductionmentioning
confidence: 99%